Medico-psychological supporting program of the multiple sclerosis patients: organization stages and tasks - E. L. Nikolaev; T. A. Karavaeva; N. V. Vasilieva; A. V. Vasilieva; E. I. Chekhlaty (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
The article presents a supporting medico-psychological program for multiple sclerosis patients that can be used in the framework of center specialized in MS treatment. It encompasses the definition of medico-psychological support of MS and presents the content of psycho-social interventions depending not only on the MS stage but also on the interrelationship of the MS period and patients mental and physical capacities. The supporting program consists of four consequent stages: information-diagnostic, psycho-correction, psychotherapy, psycho-rehabilitation. Implementation of each stage has its specific tasks, interventions and specialists team. The defined stages of the supporting program allow the specialists to provide personalized intensity and specific of psycho-social interventions and also elaborate a long-term treatment plan for each patient.